Cobalt nickel phosphate, indium zinc sulfide and cobalt oxide composite photocatalyst as well as preparation method and application thereof
By building Ni2copox@znin2s4@COOX composite photocatalyst, controlling photocopy of photoretitude and surface oxidation reaction kinetics, the problem of limited activity of pure Znin2S4 photocatalyst, significantly improved the performance of full decomposition of hydrogen -based hydrogen.
Patent Information
- Application Number
- CN202411530074.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The photogenerated electrons and holes of pure ZnIn2S4 photocatalysts are prone to recombination, resulting in limited photocatalytic reaction activity, low hole mobility and slow surface oxidation kinetics, which limit their fully decomposed water hydrogen production performance.
Construct Ni2CoPOx@ZnIn2S4@CoOx composite photocatalyst, and control photogenerated hole kinetics and surface oxidation reaction kinetics through Ni2CoPOx and CoOx.
The hydrogen production performance of ZnIn2S4 in total water decomposition is significantly improved, the hydrogen production rate reaches 1541.2 μmol·g-1·h-1, and the hydrogen peroxide production rate reaches 1381.1 μmol·g-1·h-1.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalysis, and in particular relates to a cobalt nickel phosphate@indium zinc sulfide@cobalt oxide composite photocatalyst, a preparation method and application thereof. Background Art
[0002] Using solar energy to decompose water to produce hydrogen can directly convert solar energy into chemical energy, and is one of the ideal methods to solve the energy crisis. ZnIn2S4 (ZIS) is one of the most common photocatalysts with the advantages of suitable band gap, large surface area and simple preparation method. However, the photogenerated electrons and holes of pure ZIS are easy to recombine, which seriously limits its photocatalytic reaction activity. The mass of photogenerated holes in ZIS is much larger than that of photogenerated electrons, resulting in the mobility of holes being much lower than that of electrons. At the same time, the surface oxidation reaction is a four-electron or two-electron reaction with slow kinetics. Therefore, the photocatalytic water splitting performance of ZIS is limited by the slow hole migration rate and slow surface oxidation kinetics. Therefore, the construction of Ni2CoPO x @ZnIn2S4@CoO x Composite photocatalyst, using Ni2CoPO x and CoO x By regulating the kinetics of photogenerated holes and surface oxidation reactions, it is expected to significantly improve the performance of ZIS in producing hydrogen by fully splitting water. Summary of the invention
[0003] The object of the present invention is to provide a nickel cobalt phosphate @ indium zinc sulfide @ cobalt oxide (Ni2CoPO x @ZnIn2S4@CoO x ) Composite photocatalyst, its preparation method and application.
[0004] Based on the above purpose, the present invention adopts the following technical solutions: A Ni2CoPO x @ZnIn2S4@CoO x The preparation method of the composite photocatalyst comprises the following steps: (1) dissolving a nickel source compound and a cobalt source compound in deionized water to form a solution A, dissolving a phosphine source compound in deionized water to form a solution B, and mixing the two solutions A and B; (2) reacting the mixed solution obtained in step (1) at 80 to 200° C. for 2 to 24 hours; (3) Centrifuge the product obtained in step (2), collect the solid, wash, dry, and calcine to obtain Ni2CoPO x ; (4) Ni2CoPO obtained in step (3) x adding into the ZnIn2S4 precursor solution to obtain a mixed solution; (5) reacting the mixed solution obtained in step (4) at 50°C to 200°C for 2 to 24 hours; (6) Centrifuge the product obtained in step (5), collect the solid, wash, and dry to obtain Ni2CoPO x @ZnIn2S4 composite photocatalyst; (7) Prepare Ni2CoPO in step (6) x @ZnIn2S4 composite photocatalyst was added to a mixed solution of polyvinyl pyrrolidone, deionized water and methanol, stirred to dissolve, and then tributylphosphine and cobalt source compound solution were added dropwise in sequence. After the addition was completed, stirring was continued for more than 1 hour; (8) Centrifuge the product obtained in step (7), collect the solid, wash, and dry to obtain Ni2CoPO x @ZnIn2S4@CoO x Composite photocatalyst.
[0005] Furthermore, in step (1), the molar ratio of the nickel source compound, the cobalt source compound and the phosphine source compound is (4-8): (1-2): (1-2); in step (3), the calcination temperature is 250-350°C.
[0006] Furthermore, in step (1), the nickel source compound is selected from one or a mixture of any two or more of nickel acetate tetrahydrate, nickel oxide, nickel sulfate, nickel hydroxide, nickel chloride, and nickel bromide, and the concentration of the nickel source compound in deionized water is 0.1 mmol / L to 5 mol / L; the cobalt source compound is selected from one or a mixture of any two or more of cobalt acetate tetrahydrate, cobalt nitrate hexahydrate, cobalt chloride, cobalt sulfate, cobalt oxalate, and cobalt carbonate, and the concentration of the cobalt source compound in deionized water is 0.1 mmol / L to 5 mol / L; the phosphine source compound is selected from one or a mixture of any two or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and phosphoric acid, and the concentration of the phosphine source compound in deionized water is 0.1 mmol / L to 5 mol / L.
[0007] Preferably, in step (1), the nickel source compound is selected from nickel acetate tetrahydrate, and the concentration of nickel acetate tetrahydrate in deionized water is 0.01 mol / L to 0.1 mol / L, specifically, the concentration of nickel acetate tetrahydrate in deionized water is 66.7 mmol / L; the cobalt source compound is selected from cobalt acetate tetrahydrate, and the concentration of cobalt acetate tetrahydrate in deionized water is 0.01 mol / L to 0.05 mol / L, specifically, the concentration of cobalt acetate tetrahydrate in deionized water is 33.3 mmol / L; the phosphine source compound is selected from ammonium dihydrogen phosphate, and the concentration of the phosphine source compound in deionized water is 0.01 mol / L to 0.05 mol / L; specifically, the concentration of ammonium dihydrogen phosphate in deionized water is 33.3 mmol / L.
[0008] Furthermore, the drying in step (3) refers to drying at 60°C.
[0009] Furthermore, in step (4), Ni2CoPO x The mass ratio of ZnIn2S4 is (0.5%~3.0%):1.
[0010] Furthermore, in step (4), the preparation process of the ZnIn2S4 precursor solution is as follows: take deionized water, adjust the pH to 2-3 with hydrochloric acid, dissolve the zinc source compound, the indium source compound and the sulfur source compound in a molar ratio of (1-2):(2-4):(4-8) in deionized water, and then add glycerol. The concentration of hydrochloric acid is 1-5 mol / L, and the volume ratio of deionized water to glycerol is 4:1.
[0011] Furthermore, the zinc source compound is selected from one or a mixture of any proportion of zinc chloride, zinc nitrate, zinc acetate, zinc carbonate, zinc sulfate, zinc hydroxide and zinc oxalate, and the concentration of the zinc source compound in the mixed solvent of deionized water and glycerol is 0.001 mol / L to 10 mol / L, preferably zinc chloride, and the concentration of zinc chloride in the mixed solvent of deionized water and glycerol is 0.01 mol / L to 0.05 mol / L.
[0012] Furthermore, the indium source compound is selected from one or a mixture of any proportion of indium nitrate, indium chloride, indium sulfate, indium acetate and indium oxide, and the concentration of the indium source compound in the deionized water and glycerol mixed solvent is 0.001 mol / L to 10 mol / L; indium nitrate is preferred, and the concentration of indium nitrate in the deionized water and glycerol mixed solvent is 0.02 mol / L to 0.10 mol / L.
[0013] Furthermore, the sulfur source compound is selected from one or a mixture of two or more of thioacetamide, sulfur powder, thiourea and ammonium sulfide in any proportion, and the concentration of the sulfur source compound in the deionized water and glycerol mixed solvent is 0.001 mol / L to 10 mol / L. Preferably, thioacetamide is selected from a concentration of 0.04 mol / L to 0.20 mol / L in the deionized water and glycerol mixed solvent.
[0014] Furthermore, the drying in step (6) refers to drying at 60° C. for 12 hours.
[0015] Furthermore, in step (7), the cobalt source compound is selected from one or a mixture of any proportion of cobalt acetate tetrahydrate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt sulfate, cobalt oxalate, and cobalt carbonate, and the concentration of the cobalt source compound solution is 0.001 mol / L to 10 mol / L. Cobalt chloride hexahydrate is preferred, and the concentration of the cobalt chloride hexahydrate solution is 0.001 mol / L to 10 mol / L.
[0016] Furthermore, in step (7), polyvinyl pyrrolidone, Ni2CoPO x @ZnIn2S4 photocatalyst, tributylphosphine and cobalt source compound ratio is (1~3)g:0.2g:(1~2)mL:(0.002~0.005)mmol. In step (7), the volume ratio of deionized water and methanol is 1:1, Ni2CoPO x @The concentration of ZnIn2S4 photocatalyst in ionized water and methanol is 0.1~0.5mg / mL.
[0017] Ni2CoPO prepared by the above preparation method x @ZnIn2S4@CoO x Composite photocatalyst.
[0018] The above Ni2CoPO x @ZnIn2S4@CoO x Application of composite photocatalysts in photocatalytic water splitting.
[0019] Preferably, when photocatalytically splitting water, a 300 W xenon lamp (λ>400 nm) is used as the light source, Ni2CoPO x @ZnIn2S4@CoO x The concentration of the composite photocatalyst in water is 0.01 mg / mL ~1 mg / mL.
[0020] Beneficial effects of the present invention: Ni2CoPO x and CoO x The clusters can serve as active sites for water oxidation to produce hydrogen peroxide. x and CoO x The introduction of clusters can effectively improve the separation efficiency of photogenerated carriers, enhance the light absorption capacity, and thus significantly improve the photocatalytic water splitting performance. x @ZnIn2S4@CoO x The hydrogen production rate of the composite photocatalyst is 1541.2 μmol·g -1 ·h -1 The hydrogen peroxide production rate reached 1381.1 μmol·g -1 ·h-1 In addition, the Ni2CoPO x @ZnIn2S4@CoO x The composite photocatalyst has the advantages of simple preparation method and easy control of preparation conditions, and has certain research and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the X-ray diffraction pattern of the photocatalyst prepared in Example 1, Example 2, Example 3 and Example 4 of the present invention; Figure 2 The (a) ZnIn2S4, (b) CoO prepared in Example 1, Example 2, Example 3 and Example 4 of the present invention x @ZnIn2S4, (c) Ni2CoPO x @ZnIn2S4 and (d) Ni2CoPO x @ZnIn2S4@CoO x SEM images, the scale bars are all 1 μm; Figure 3 is the ultraviolet-visible light absorption spectra of the photocatalysts prepared in Example 1, Example 2, Example 3 and Example 4 of the present invention; Figure 4 is a steady-state fluorescence spectrum diagram of the photocatalyst prepared in Example 1, Example 2, Example 3 and Example 4 of the present invention; Figure 5 Graph showing the photocatalytic total water decomposition rates of the photocatalysts prepared in Example 1, Example 2, Example 3 and Example 4 of the present invention. DETAILED DESCRIPTION
[0022] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below with reference to the relevant drawings. The drawings show preferred embodiments of the present invention, but are not limited to the embodiments described herein.
[0023] Embodiment 1 Preparation of ZnIn2S4 photocatalyst: Take 96 mL of deionized water and adjust its pH to about 2.5 with 3 mol / L dilute hydrochloric acid. After mixing evenly, add zinc chloride (ZnCl2, 545 mg, 4 mmol), indium chloride tetrahydrate (InCl3·4H2O, 1173 mg, 4 mmol), thioacetamide (TAA, 601 mg, 8 mmol) in sequence, and finally add 24 mL of glycerol and stir until the drugs are completely dissolved. React at 80 °C for 2 h, cool and precipitate, centrifuge, take the solid, wash with deionized water and anhydrous ethanol in sequence, and then dry in a vacuum drying oven at 60 °C for 12 h. Collect the powder sample obtained after drying, which is the ZnIn2S4 photocatalyst.
[0024] Embodiment 2 CoO x @ZnIn2S4 composite photocatalyst preparation: Polyvinyl pyrrolidone (PVP, 2g), 50 mL of deionized water and 50 mL of methanol solution were mixed evenly, and then 200 mg of photocatalyst ZnIn2S4 was added and stirred at room temperature for 1 h. 1 mL of tributylphosphine (TBP) was added, and after stirring for 5 min, 3.5 mL of CoCl2 solution (concentration of 2 mM) was added dropwise and stirred for 1 h. After centrifugation, the precipitation was washed twice with anhydrous ethanol and deionized water respectively, and dried under vacuum at 60 °C for 12 h to obtain CoO x @ZnIn2S4 composite photocatalyst.
[0025] Embodiment 3 Ni2CoPO x @ZnIn2S4 composite photocatalyst preparation: 4 mmol Ni(CH3COO)2·4H2O and 2 mmol Co(CH3COO)2·4H2O were dissolved in 30 mL deionized water to form solution A; 2 mmol NH4H2PO4 was dissolved in 30 mL deionized water to form solution B. Solution A was added dropwise to solution B under stirring and stirred for a certain period of time. Heat at 120 °C for 4 h. After cooling, centrifuge and collect the solid, wash it twice with deionized water and anhydrous ethanol respectively, then vacuum dry it at 60 °C for 12 h, and anneal the sample in air at 300 °C for 3 h to obtain Ni2CoPO x Take 96 mL of deionized water and adjust its pH to about 2.5 with 3 mol / L dilute hydrochloric acid. After the solution is mixed evenly, add 17 mg of the previously prepared Ni2CoPO xUltrasonic dispersion was performed, and zinc chloride (ZnCl2, 545 mg, 4 mmol), indium chloride tetrahydrate (InCl3·4H2O, 1173 mg, 4 mmol), thioacetamide (TAA, 601 mg, 8 mmol) were added in sequence, and finally 24 mL of glycerol was added and stirred until the drugs were completely dissolved. The reaction was carried out at 80 °C for 2 h, and the solid was centrifuged after cooling and precipitation, and then washed with deionized water and anhydrous ethanol in sequence, and then vacuum dried at 60 °C for 12 h. The powder sample obtained after drying was collected as Ni2CoPO x @ZnIn2S4 photocatalyst.
[0026] Embodiment 4 Ni2CoPO x @ZnIn2S4@CoO x Preparation of composite photocatalyst: Polyvinyl pyrrolidone (PVP, 2 g), 50 mL of deionized water and 50 mL of methanol solution were mixed evenly, and 200 mg of Ni2CoPO4 was added. x @ZnIn2S4 and stir evenly, add 1 mL of tributylphosphine (TBP) solution, stir for 5 min, then add 3.5 mL of CoCl2 solution (concentration is 2 mM) dropwise, and continue stirring for 1 h. After centrifugation, wash twice with anhydrous ethanol and deionized water respectively, dry under vacuum at 60 °C for 12 h, and collect the dried sample to obtain Ni2CoPO x @ZnIn2S4@CoO x Composite photocatalyst.
[0027] The photocatalysts obtained from Examples 1 to 4 were characterized in various ways. Figures 1 to 5 It is the characterization result of the structure and performance of the photocatalyst. Figure 1 It can be seen that ZnIn2S4 prepared in Example 1 has a higher CoO x The XRD spectrum of ZnIn2S4 composite photocatalyst is almost the same as that of single ZnIn2S4. x @ZnIn2S4 and Ni2CoPO x @ZnIn2S4@CoO x The XRD spectrum of the composite photocatalyst is almost the same as that of single ZnIn2S4, which indicates that CoO x Clusters and Ni2CoPO x The introduction of did not change the crystal structure and phase composition of ZnIn2S4. Figure 2 (a) It can be seen that the morphology of ZnIn2S4 prepared in Example 1 is a flower-like microsphere structure composed of nanosheets. Figure 2(b) It was observed that the CoO prepared in Example 2 x @ZnIn2S4 is still a flower-like microsphere structure, CoO x The introduction of clusters did not affect the morphology and structure of ZnIn2S4. Figure 2 (c) shows Example 3, introducing Ni2CoPO x Afterwards, the morphology of the composite sample changed significantly. x The morphology of @ZnIn2S4 composite photocatalyst is mainly composed of two types, one is a large flake structure and the other is a flower-like microsphere structure. Figure 2 (d) shows Example 4, in Ni2CoPO x @ZnIn2S4 further loaded with CoO x After clustering, its morphology did not change further, and it still maintained the large flake structure and flower-like microsphere structure. Figure 3 It can be seen that the absorption band edge of ZnIn2S4 is around 500 nm. x The introduction of clusters improves the light absorption capacity at 560-800 nm, and Ni2CoPO x The introduction of Ni2CoPO x @ZnIn2S4 and Ni2CoPO x @ZnIn2S4@CoO x The light absorption capacity in the ultraviolet region is significantly enhanced and the light absorption band edge is blue-shifted. Figure 4 It can be seen that ZnIn2S4 exhibits a strong fluorescence peak, indicating that the photogenerated carrier recombination of ZnIn2S4 is serious. X Clusters and Ni2CoPO x The fluorescence intensity of the photogenerated carriers was effectively reduced by the introduction of CoO X Clusters and Ni2CoPO x The fluorescence intensity of the composite material is lower, which further indicates that CoO X Clusters and Ni2CoPO x Both can effectively separate photogenerated carriers.
[0028] The full water decomposition experiment was carried out in a closed quartz reactor. A 300 W xenon lamp (λ>400 nm) was used as the light source, and 275 mL of distilled water was used as the reaction solution. The photocatalysts prepared in Examples 1 to 4 were added, and the amount of photocatalyst was 10 mg. Before the experiment, the closed reactor was evacuated for about 30 minutes to remove the air. After the reaction was completed, 5 mL of supernatant was taken by centrifugation of the reaction solution, 5 mL of 1.2 mM H2SO4 solution and 5 mL of 0.1 mM KMnO4 solution were added, and after mixing for 5 to 10 minutes, the light absorption test of the solution was performed on a UV-visible spectrophotometer (UV-2600, Shimadzu, Japan). The molar amount of H2O2 was calculated according to the fitting formula. The chemical equation is as follows: 2MnO 4- + 5H2O2+ 6H + → 2Mn 2+ + 5O2↑+8H2O The performance results of water splitting are as follows Figure 5 As shown. Figure 5 It can be seen that the rate of hydrogen and hydrogen peroxide production of pure ZnIn2S4 is low, mainly due to the low efficiency of photogenerated carrier separation and the lack of effective oxidation active sites. X Clusters and Ni2CoPO x The introduction of can significantly improve the photocatalytic water splitting performance. x @ZnIn2S4@CoO x The composite photocatalyst has the highest performance, with a hydrogen production rate of 1541.2 μmol / g / h and a H2O2 production rate of 1381.1 μmol / g / h, with the ratio of the two close to 1:1. The performance improvement comes from the improved separation and migration efficiency of photogenerated carriers and the CoO x Clusters and Ni2CoPO x can serve as oxidation active sites.
[0029] Based on the above ideal implementation of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the content of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A Ni2CoPO x @ZnIn2S4@CoO x The method for preparing a composite photocatalyst is characterized in that: The following steps are involved: (1) dissolving a nickel source compound and a cobalt source compound in deionized water to form a solution A, dissolving a phosphine source compound in deionized water to form a solution B, and mixing the two solutions A and B; (2) reacting the mixed solution obtained in step (1) at 80 to 200° C. for 2 to 24 hours; (3) Centrifuge the product obtained in step (2), collect the solid, wash, dry, and calcine to obtain Ni2CoPO x ; The Ni2CoPO obtained in step (3) x adding into the ZnIn2S4 precursor solution to obtain a mixed solution; (5) reacting the mixed solution obtained in step (4) at 50°C to 200°C for 2 to 24 hours; (6) Centrifuge the product obtained in step (5), collect the solid, wash, and dry to obtain Ni2CoPO x @ZnIn2S4 composite photocatalyst; (7) Prepare Ni2CoPO in step (6) x @ZnIn2S4 composite photocatalyst was added to a mixed solution of polyvinyl pyrrolidone, deionized water and methanol, stirred to dissolve, and then tributylphosphine and cobalt source compound solution were added dropwise in sequence. After the addition was completed, stirring was continued for more than 1 hour; (8) Centrifuge the product obtained in step (7), collect the solid, wash, and dry to obtain Ni2CoPO x @ZnIn2S4@CoO x Composite photocatalyst.
2. Ni2CoPO according to claim 1 x @ZnIn2S4@CoO x The method for preparing a composite photocatalyst is characterized in that: In step (1), the molar ratio of the nickel source compound, the cobalt source compound and the phosphine source compound is (4-8): (1-2): (1-2); in step (3), the calcination temperature is 250-350°C.
3. Ni2CoPO according to claim 1 x @ZnIn2S4@CoO x The method for preparing a composite photocatalyst is characterized in that: In step (1), the nickel source compound is selected from one or a mixture of any two or more of nickel acetate tetrahydrate, nickel oxide, nickel sulfate, nickel hydroxide, nickel chloride, and nickel bromide, and the concentration of the nickel source compound in distilled water is 0.1 mmol / L to 5 mol / L; the cobalt source compound is selected from one or a mixture of any two or more of cobalt acetate tetrahydrate, cobalt nitrate hexahydrate, cobalt chloride, cobalt sulfate, cobalt oxalate, and cobalt carbonate, and the concentration of the cobalt source compound in distilled water is 0.1 mmol / L to 5 mol / L; the phosphine source compound is selected from one or a mixture of any two or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and phosphoric acid, and the concentration of the phosphine source compound in distilled water is 0.1 mmol / L to 5 mol / L.
4. Ni2CoPO according to claim 1 x @ZnIn2S4@CoO x The method for preparing a composite photocatalyst is characterized in that: In step (4), Ni2CoPO x The mass ratio of ZnIn2S4 is (0.5%~3.0%):
1.
5. Ni2CoPO according to claim 1 x @ZnIn2S4@CoO x The method for preparing a composite photocatalyst is characterized in that: In step (4), the preparation process of the ZnIn2S4 precursor solution is as follows: take deionized water, adjust the pH to 2-3 with hydrochloric acid, dissolve the zinc source compound, the indium source compound and the sulfur source compound in a molar ratio of (1-2):(2-4):(4-8) in deionized water, and then add glycerol.
6. Ni2CoPO according to claim 5 x @ZnIn2S4@CoO x The method for preparing a composite photocatalyst is characterized in that: The zinc source compound is selected from one or a mixture of two or more of zinc chloride, zinc nitrate, zinc acetate, zinc carbonate, zinc sulfate, zinc hydroxide and zinc oxalate in any proportion, and the concentration of the zinc source compound in the deionized water and glycerol mixed solvent is 0.001 mol / L to 10 mol / L; the indium source compound is selected from one or a mixture of two or more of indium nitrate, indium chloride, indium sulfate, indium acetate and indium oxide in any proportion, and the concentration of the indium source compound in the deionized water and glycerol mixed solvent is 0.001 mol / L to 10 mol / L; the sulfur source compound is selected from one or a mixture of two or more of thioacetamide, sulfur powder, thiourea and ammonium sulfide in any proportion, and the concentration of the sulfur source compound in the deionized water and glycerol mixed solvent is 0.001 mol / L to 10 mol / L.
7. Ni2CoPO according to claim 1 x @ZnIn2S4@CoO x The method for preparing a composite photocatalyst is characterized in that: In step (7), the cobalt source compound is selected from one or a mixture of any proportion of cobalt acetate tetrahydrate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt sulfate, cobalt oxalate, and cobalt carbonate, and the concentration of the cobalt source compound solution is 0.001 mol / L to 10 mol / L.
8. Ni2CoPO according to claim 1 x @ZnIn2S4@CoO x The method for preparing a composite photocatalyst is characterized in that: In step (7), polyvinyl pyrrolidone, Ni2CoPO x @The ratio of ZnIn2S4 photocatalyst, tributyl phosphine and cobalt source compound is (1~3) g:0.2 g:(1~2) mL:(0.002~0.005) mmol.
9. Ni2CoPO prepared by the preparation method according to any one of claims 1 to 8 x @ZnIn2S4@CoO x Composite photocatalyst.
10. Ni2CoPO according to claim 9 x @ZnIn2S4@CoO x Application of composite photocatalysts in photocatalytic water splitting.
Citation Information
Patent Citations
Method for preparing cobalt nickel phosphate microsphere material
CN113184823A
RuOx / Ru-indium zinc sulfide composite photocatalyst as well as preparation method and application thereof
CN116984002A
Bacillus velezensis PGR-1 and uses thereof
KR1020250058203A